PA’ANG BELE: LOCUS KEHIDUPAN KEKAL MASYARAKAT MANGGARAI - Jebarus, Adrianus (STKIP Santu Paulus Ruteng, 2015)
Abstract: Pa'ang Bele: Locus of Eternal Life Manggarain Society. Man is he who seek, pursue, submitters, dreaming and creating the history of his own life. Humans are composed of body and soul continue to struggle to achieve the fullness of himself. The fullness of himself that was started and experienced the fullness of him now but sempurnan place in the afterlife. Eternal life will be obtained only through and in death. Death is a transition from life forms is now headed for a new life, eternal life. Pa'ang bele is a locus, and eternal life or situation according to Manggarain community. In the pa'ang bele human experience having the fullness of himself in there along with others harmoniously together with Morin agu Ngaran. Keywords: life, death, eternal life Abstrak: Pa’ang Bele: Locus Kehidupan kekal Masyarakat Manggarai. Manusia adalah dia yang mencari, mengejar, menyerahkan diri, bermimpi dan menciptakan sejarah hidupnya sendiri. Manusia yang terdiri dari badan dan jiwa terus berjuang untuk mencapai kepenuhan dirinya. Kepenuhan diri itu sudah dimulai dan dialami sekarang tetapi kepenuhannya yang sempurnan baru terjadi di akhirat. Kehidupan kekal akan diperoleh hanya melalui dan dalam kematian. Kematian merupakan peralihan dari bentuk kehidupan sekarang menuju kehidupan baru, kehidupan abadi. Pa’ang bele merupakan locus dan atau situasi kehidupan kekal menurut masyarakat Manggarai. Di pa’ang bele manusia mengalami kepenuhan dirinya dalam ada bersama dengan yang lain secara harmonis bersama dengan Morin agu Ngaran. Kata kunci: kehidupan, kematian, hidup kekal